Malignant mesothelioma incidence by nation-wide cancer registry: a population-based study. - Tomasson, Kristinn; Gudmundsson, Gunnar; Briem, Haraldur; Rafnsson, Vilhjalmur (Journal of Occupational Medicine and Toxicology, 2016)
To access publisher's full text version of this article, please click on the hyperlink in Additional Links field or click on the hyperlink at the top of the page marked Files. This article is open access. Malignant mesothelioma caused by asbestos exposure has a long latency period. A ban on asbestos use may not be apparent in decreased incidence in the population until after several decades. The aim was to evaluate changes in the incidence of malignant mesothelioma, and the possible impact of the asbestos ban implemented in Iceland in 1983. This is a population study on aggregate level; the source of data was the Icelandic Cancer Registry, the National Cause-of-Death Registry, and the National Register. Volume of asbestos import was obtained from Customs Tariff. The import figures reflect fairly accurately the amount used, as there are no mines in the country. Asbestos import peaked in 1980 at 15.0 kg/capita/year, diminishing to 0.3 kg/capita/year ten years after the ban in 1983, and to zero in the most recent years. Seventy-nine per cent of the cases of malignant mesothelioma were men, and 72 % were of pleural origin. Mesothelioma incidence increased steadily from 1965 to 2014, when it reached 21.4 per million among men, and 5.6 among women. Mortality in 2014 was 22.2 per million among men, and 4.8 among women. Malignant mesothelioma incidence and mortality increased in the population during the period, despite the ban on asbestos use from 1983. This is in agreement with the long latency time for malignant mesothelioma. In line with the previously high per capita volume of asbestos import, many buildings, equipment, and structures contain asbestos, so there is an on-going risk of asbestos exposure during maintenance, renovations and replacements. It is thus difficult to predict when the incidence of malignant mesothelioma will decrease in the future. During the last ten-year period, the incidence in Iceland was higher than the recently reported incidence in neighbouring countries.